Determination of the half-life and the absolute photon emission intensities for the main gamma-ray energies of 124I. (January 2021) - Pibida, L.; Bergeron, D.E.; Zimmerman, B.; Fitzgerald, R.; Cessna, J.T.; King, L.
Abstract: The National Institute of Standards and Technology (NIST) performed new standardization measurements for 124 I. As part of this work the absolute photon emission intensity for the main gamma-rays of 124 I were determined using several high-purity germanium (HPGe) detectors. In addition, the half-life for 124 I was also determined using an HPGe detector. Ionization chamber measurements were performed for additional sources, but it was not possible to obtain a precise half-life value. Highlights: Measurements of photon emission probabilities of 124 I. Measurement of 124 I half-life. High-purity germanium detectors for gamma-ray spectrometry measurements.